2007
DOI: 10.1007/s00268-007-9011-9
|View full text |Cite
|
Sign up to set email alerts
|

Gallstone Ileus: Diagnosis and Management

Abstract: Gallstone ileus is a difficult clinical entity to diagnose. Unreserved use of imaging techniques can improve diagnostic accuracy and speed of therapeutic decision making. Management of gallstone ileus must be individualized. The one-stage procedure should be offered only to highly selected patients with good cardiorespiratory reserve and with absolute indications for biliary surgery at the time of presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
274
0
33

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(308 citation statements)
references
References 35 publications
1
274
0
33
Order By: Relevance
“…Rigler’s triad of pneumobilia, an ectopic gallstone, and dilated small bowel on abdominal x-ray is classic but is only seen in 30%–35% of cases [6]. Classic CT scan findings are pneumobilia, cholecystoduodenal fistula and a gallstone in the duodenum [2,3,15]. Although, 15%–25% of gallstones cannot be visualized on CT scan as they can be isoattenuating.…”
Section: Discussionmentioning
confidence: 99%
“…Rigler’s triad of pneumobilia, an ectopic gallstone, and dilated small bowel on abdominal x-ray is classic but is only seen in 30%–35% of cases [6]. Classic CT scan findings are pneumobilia, cholecystoduodenal fistula and a gallstone in the duodenum [2,3,15]. Although, 15%–25% of gallstones cannot be visualized on CT scan as they can be isoattenuating.…”
Section: Discussionmentioning
confidence: 99%
“…Delay in the diagnosis of GI has a high morbidity and mortality rates. Ayantunde et al [4] reported that an average presentation of these patients to the hospital 3 days from symptom onset. Consistent with these findings, in our case, patient was admitted with nausea, abdominal pain and bilious vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…Plain abdominal radiographs may reveal signs of small-bowel obstruction and concomitant aerobilia, which is also supportive of gallstone ileus 9 . However, the diagnosis of gallstone ileus is still frequently missed or delayed, and an accurate preoperative diagnosis is made in only 77 of cases 10 . The classical radiological triad for this diagnosis is pneumobilia, the presence of an ectopic gallstone, and mechanical bowel obstruction 11 .…”
Section: Discussionmentioning
confidence: 99%